Determining therapeutic trough ranges for linezolid - Abdullah Alsultan (Elsevier, 2019)
Linezolid (LZD) is an oxazolidinone approved for the treatment of gram-positive infections. Therapeutic drug monitoring is increasingly used to optimize LZD dosing. The therapeutic target for LZD is to achieve an area under the concentration-time curve over 24 h divided by the MIC (AUC/MIC) > 100. In this study, we determined the trough ranges associated with this therapeutic AUC. Concentration-time profiles for 999 virtual patients were simulated using a previously published pharmacokinetic model for LZD. AUC was estimated for each virtual patient using the trapezoidal method. We determined the trough ranges that achieve the therapeutic target of AUC/MIC > 100 at different MIC values of 1, 2 and 4 μg/mL. Trough samples correlated well with LZD AUC (R2 = 0.87). For trough concentration of 2-5 μg/mL, 99% had an AUC0-24 > 100 µg⋅h⋅ml−1, 23% had an AUC0-24 > 200 µg⋅h⋅ml−1 and none had an AUC0-24 > 400 µg⋅h⋅ml−1. For trough concentrations of 5-8 µg/ml, 87% of the patients had an AUC0-24 > 200 µg⋅h⋅ml−1 and none had an AUC0-24 > 400 µg⋅h⋅ml−1 To achieve the therapeutic target of an AUC/MIC > 100, it is suggested that trough ranges be set at 2-5 µg/ml if the MIC < 2 and 5-8 µg/ml if the MIC = 2; however, at an MIC of 4 µg/ml, it is difficult to achieve an AUC/MIC > 100 without increasing the risk of LZD toxicity. Keywords: Linezolid, Therapeutic drug monitoring, Pharmacokinetics